Understanding Differences on Using SME’s Web Before and After the Training of SME’s Website Operation (A Case Study of Implementing SME’s Website of Banguntapan and Imogiri) - Tri Siwi Nugrahani; Setia Wardani; Wibawa Wibawa (Journal of Economics, Business, and Accountancy Ventura, 2017)
This research attempts to test the level of understanding of using website as a marketing media for the agents of SME’s by employing 65 SME’s agents. They have been legalized and have joined the training of website operating in 2016 and 2017. The sample consists of 25 agents of SME’S from Banguntapan and 44 agents from Imogiri. The hypothesis is related to the existence of difference on understanding SME’s website after and before conducting the training of website operating. Based on the analysis of Paired Sample Test by comparing the respond of SME’s agents before and after the training of website operating, it shows that t value -9,282 by 0, 000 significance. It reveals that the training to increase the level of understanding of using website was effectively resulted. It comes to the fact that this activity can increase the selling percentage. The item of new website is expected to be beneficial to increase product selling effectively which has been conducted by SME’S agents.